A Novel Position-Based Impedance Control Method for Bionic Legged Robots’ HDU - Kai-Xian Ba (IEEE Access, 2018)
In this paper, a novel impedance control method is designed for the hydraulic drive unit (HDU) equipped on the hydraulic driven legged robot. First, the position control mathematical model of HDU is built. Next, the HDU performance test platform is introduced and the performance requirements are given. Second, the system load pressure observer is designed and an accurate stiffness control method is proposed by combining the external load force feed forward control with the load force feedback control. Third, the damping control method based on the velocity feedback is designed. Finally, a novel impedance control method is proposed through combining the stiffness control and the damping control. The effects of all techniques listed above have been verified experimentally. Especially, the impedance control effects are verified by comparing the impedance characteristics with the natural characteristics of the secondorder mass-spring-damper system. This research indicates that the system characteristics of HDU with the novel impedance control method is well equivalent to that of the second-order mass-spring-damper system, which can solve the stall problem of the robot joint movement process caused by the load force vanish instantaneously and the switch between position control and force control. The above research can provide references for the active compliance control of bionic legged robots.